Influence of rearing method on the behaviour and welfare of Assaf lambs during the neonatal period - SIMEONOV, MIROSLAV; HARMON, DAVID L; STOYCHEVA, INA (The Indian Journal of Animal Sciences, 2024)
The present study aimed to determine the influence of rearing method on behaviour and welfare in Assaf lambs during the first two weeks of the neonatal period, in an intensive rearing system. The experiment was conducted with 24 Assaf lambs, in which two methods of management were applied – natural rearing (NR) and artificial rearing (AR). Forced separation of lambs from their mothers caused 74% fewer suckling attempts during the first three days of the neonatal period, which reduced suckling time by 57%. The lambs reared under NR, spent more time moving and less time standing and lying. Overall, it was found that the type of rearing affects the suckling time. Artificial rearing decreased lying and playing time, which is indicative of the improved welfare of NR lambs. The two rearing methods (NR and AR) did not affect blood total protein or albumin, indicating no significant effect of different rearing methods on these haematological variables. Artificial rearing does not disturb the welfare and behaviour of the animals when it is done correctly and stress appears transient and animals quickly adapt with similar growth rates.